A Study of the Cognitive Synesthetic Mechanism as a Supplement to the Sound Imitation Theory of Lingual Genesis - Lavrynenko, Oleksandr (East European Journal of Psycholinguistics, 2015)
In this article, an analytical view of the general theories of language genesis is presented. The evolutional, idealistic and cognitive approaches to the exploration of language origins are described in the theoretical part. At the end of this part the author explains the meaning and origin of the term "synesthesia" and demonstrates the foundation of its practical reasonability. In the practical part of work an empirical study of the phenomenon of synesthesia is carried out, based on literary Ukrainian-language material. The phenomenon referred to is considered to have been one of the sources of the creation of new words during the development of civilization. It is ascertained that synesthesia is a genuine phenomenon which, in the author’s opinion, is able to reinforce the sound imitation theory of language genesis, along with the concept of memes. References Vygotsky, L. (1982a). Voprosy Teoriyi i Istoriyi Psihologiyi [Issues of Theory and History of Psychology]. Moscow: Pegagogika. Vygotsky L. (1982b). Voprosy Obshchey Psihologiyi [Issues of General Psychology]. Moscow: Pegagogika. Hobbes, Th. (2000). Leviafan abo Sut, Budova i Povnovazhennia Derzhavy [Leviathan, or Essence, Construction and Functions of State]. Kyiv: Dukh i Litera. Zalevskaya A. (2000). Vvedeniye v Psiholingvistiku [Introduction to Psycholinguistics]. Moscow: Russian State University for the Humanities. Krasnykh, V. (2001) Osnovy Psiholingvistiki i Teorii Kommunikatsii [Foundations of Psycholinguistics and Theory od Communication]. Moscow: Gnosis. Leontyev, A. A. (2003). Osnovy Psiholingvistiki [Foundations of Psycholinguistics]. Moscow: Smysl. Leontyev, A. N. (1963). Vozniknoveniye i Razvitiye Yazyka [Language Emergence and Development]. Moscow: AN USSR. Leontyev, A. N. (2004). Deyatelnost, Soznanye, Lichnost [Activity, Consciousness, Personality]. Moscow: Smysl. Luriya, A.R. (2006). Osnovy Neyropsyhplogii [Foundations of Neuropsychology]. Moscow: Akademija. Luriya, A. R. (1979). Yazyk i Soznaniye [Language and Consciousness]. Moscow: Moscow University Publishing. Malinovsky, B. (1988). Pervobytnyie Kultury [Primitive Cultures]. Moscow: Nauka.